Mailing Lists Archives Analyzer - Rzecki, Krzysztof; Riegel, Maximilian (Studia Informatica. System and information technology, 2006)
Article describes chance to explore data hidden in headers of e-mails taken from archive of mailing lists. Scientist part of the article presents a way of transforms information enclosed in Internet resources, explains idea of mailing lists archive and points out knowledge can be taken from. Technical part presents implemented and working system analyzing headers of e-mail messages stored in mailing lists archives. Some example results of this experiment are also given.